A statistical explanation of the Dunning-Kruger effect - Jan R. Magnus; Anatoly A. Peresetsky (Tinbergen Institute, 2021)
An explanation of the Dunning-Kruger effect is provided which does not require any psychological explanation, because it is derived as a statistical artefact. This is achieved by specifying a simple statistical model which explicitly takes the (random) boundary constraints into account. This model fits the data perfectly.
Keywords: A22; C24; C91; D84; D91; I21; 330; Dunning-Kruger effect; Boundary conditions; Tobit model